Literature Review: The Effect of Knowledge and Communication, Information, and Education (CIE) on the Incidence of Anemia in Pregnant Women - Maharika, Maharika; Windayanti, Hapsari; Nurul Hidayati, Ika; Giyartiningsih, Giyartiningsih; Pujiastuti, Asri; Yuliastuti, Dyana (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Anemia in pregnant women remains a global health problem that can increase the risk of pregnancy complications and adversely affect both maternal and fetal health. The occurrence of anemia is influenced not only by biological factors but also by non-biological factors, such as maternal knowledge and Communication, Information, and Education (CIE) interventions. Adequate knowledge can promote positive health behaviors, thereby contributing to the prevention of anemia.This study aimed to analyze the effect of maternal knowledge and CIE on the incidence of anemia in pregnant women using a literature review approach. The literature search was conducted through PubMed, Google Scholar, and ScienceDirect databases, covering publications from 2017 to 2025. The keywords used included “anemia in pregnant women,” “maternal knowledge of anemia,” “health education anemia pregnancy,” and “CIE anemia.” The inclusion criteria were articles published in English or Indonesian, available in full text, and discussing the relationship between knowledge or educational interventions and anemia in pregnant women. The exclusion criteria included irrelevant articles, non–full-text articles, and duplicates. From an initial search of 30 articles, a screening process was conducted, resulting in 5 articles that met the criteria and were analyzed descriptively.The results of the review showed that 3 out of 5 articles reported a significant association between maternal knowledge and the incidence of anemia, where low knowledge increased the risk of anemia. In addition, one experimental study demonstrated that CIE interventions were effective in significantly improving maternal knowledge. However, there is still insufficient evidence to confirm that increased knowledge through CIE directly reduces the incidence of anemia, as it is influenced by other factors such as nutritional status, adherence to iron tablet consumption, and antenatal care visits.In conclusion, maternal knowledge and CIE play an important role in preventing anemia in pregnant women through improving health behaviors; however, they have not been directly proven to reduce the incidence of anemia. Therefore, more comprehensive interventions and studies with stronger research designs are needed.